COMPOSITION AND ANTIMICROBIAL ACTIVITY OF ACHILLEA FRAGRANTISSIMA ESSENTIAL OIL USING FOOD MODEL MEDIA - Alsohaili, Sohail A.; Al-fawwaz, Abdullah T. (European Scientific Journal, ESJ, 2014)
The emergence of food-borne disease combines with consumer demands for avoiding artificial food preservatives shifted the research interest to natural food preservatives such as essential oils isolated from medicinal plants which have antimicrobial activity. The aim of this study was to evaluate the efficiency of Achillea fragrantissima essential oils (E.O.) as natural food preservative in four different food model media (cheese, meat, milk, and tomato) against two gram-positive and two gram-negative bacteria (Bacillus cereus, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa) and three different food spoilage fungi using agar well diffusion method. The results showed that the maximum activity of Achillea fragrantissima E.O. was against Bacillus cereus in tomato media with relative inhibition zone diameter (RIZD) 180%, the most sensitive food spoilage fungi was Aspergillus spp. in tomato media with RIZD 150%. The results showed that there was inhibitory effect of Achillea fragrantissima E.O. against most of the tested species in different food model media which will lead to control food pathogen organisms by using E.O. as food preservative and flavoring agents.